Geomys bursaries or pocket gopher of Kansas - Pape, Charles Wesley (My University, 1895)
Introduction: In the preparation of this little work the author has endeavored to set forth, in a clear and concise manner, his experiences and observations of the Geomys bursaries. As to its usefulness, the author sees none except in special soils as described under that head. The gopher’s destructiveness, however by far exceeds that which generally calculated by the average tiller of the soil. This is principally due to the gopher’s work in so much underground that much of its depredations are hidden from the eyes of man. In giving the amounts, as paid in bounties in certain states, the author gives thanks to the Agricultural Department at Washington D.C. for the information given in bulletins #4 of the division of Ornithology and mammalogy for 93 and the authors would advise everyone interested in the subject, to consult the above bulletin and see the vast amounts that have been spent in contesting against the gopher. The author’s experience in killing the gopher extends over a period of eight years, during which time all the methods herein described have been tried and his success and opinions of each method are given under each respective method.
Citation: Pape, Charles Wesley. Geomys bursaries or pocket gopher of Kansas. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Geomys bursaries; Pocket gopher; Kansas; Mammals; Eradication; Theses; Manuscripts (documents)